Harmonizing Common Values and Theological Limits: An Islamic Perspective on Multiculturalism and Pluralism - Firanita Putri; Normuslim Normuslim; Muslimah Muslimah (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
This study aims to examine the compatibility of multiculturalism and religious pluralism within an Islamic framework by synthesizing shared human values alongside firmly established theological boundaries. Despite the growing necessity for interfaith harmony in diverse societies, confusion persists regarding how Islam distinguishes between accepting social multiculturalism and endorsing religious pluralism that relativizes truth claims. To address this issue, the research adopts a qualitative conceptual approach relying on primary textual analysis of the Qur'an, Hadith, and classical theological literature. Data collection is conducted through a structured thematic literature search focused on Islamic jurisprudence, ethics, and contemporary socio-religious discourse. The collected textual evidence is then examined using critical discourse analysis and comparative content analysis to evaluate the boundaries of religious tolerance versus doctrinal exclusivity. The findings demonstrate that Islam strongly affirms multiculturalism through the Qur'anic concept of ta'aruf and the intrinsic dignity accorded to all human beings. Furthermore, Islamic tradition provides a robust framework for shared civic values, justice, and peaceful coexistence across diverse social and ethnic backgrounds. However, the study reveals a clear theological demarcation where mainstream Islamic scholarship critiques radical religious pluralism that seeks to equate distinct theological truth claims. The analysis underscores that respecting the rights of religious minorities does not require the dilution of core Islamic creed ('aqidah). Future research should empirically investigate how local Islamic institutions operationalize these theological boundaries within everyday civic engagement in multicultural urban environments.